GnRH-agonist pretreatment in hormone replacement therapy improves pregnancy outcomes in women with male-factor infertility - Yu, Juanjuan; Chen, Peiqin; Luo, Yifan; Lv, Mu; Lou, Liqun; Xiao, Qimeng; Wang, Luxia; Chen, Juan; Bai, Mingzhu; Zhang, Zhenbo (Frontiers in Endocrinology, 2022)
Objective This study aimed to examine the efficacy of HRT with gonadotropin-releasing hormone agonist (GnRH-a) pre-treatment in women with male-factor infertility who underwent a frozen embryo transfer (FET) programme. Design Between January 2016 and October 2020, 2733 women with male-factor infertility who underwent the HRT protocol as the endometrial preparation method were enrolled at two Reproductive Medicine Centres. Patients were divided into two groups based on whether they had GnRH-a pre-treatment before HRTs: the GnRHa-HRT group and the HRT group. The inverse probability of treatment weighting (IPTW) method was conducted to balance patient baseline characteristics between treatment cohorts to reduce selection bias. The live birth rate was considered regarded as the primary pregnancy outcome. Results Multivariate logistic regression adjusted for confounding factors, the GnRHa-HRT group showed a notably higher rate of live birth (OR 2.154, 95% CI 1.636 2.835, P<0.001) when compared to the HRT group. Additionally, the rate of miscarriage was significantly lower in the GnRHa-HRT group. The GnRHa-HRT group had significantly higher rates of biochemical pregnancy, clinical pregnancy, multiple pregnancy, and term birth. Conclusion The endometrial preparation protocol of HRT with GnRH-a pre-treatment could obviously increase the live birth rate for women with male-factor infertility undergoing the FET programme.